Comparison Study Of Usd, Euro, Gold Dinar Exchange On The Rupiah Exchange In 2009 – 2012 - M. Indra Mulia Nasution; Sabaruddin Chaniago; Prof. M. Shabri A. Majid, Ph.D; Dr. Marliyah, M.A, Dr. Rita Handayani, M.Si (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to see the movement of the USD, EURO, and Gold Dinar against the Rupiah in 2019 – 2012. Analyze the fluctuations of the three currencies against the rupiah, analyze the relationship between the three currencies against the rupiah. The research population is the average value of the USD, EURO, and Gold Service currencies registered with BI for the period 2009 – 2012. The results show that the lowest value, the highest value for the Euro currency, is the standard deviation of 0.0267 and 0.0478. . From the average, the Gold dinar has the highest volatility at 0.047815 followed by the US Dollar at 0.047814. The euro currency average of the lowest volatility at the position of 0.026725. The stationarity test shows the value of the ADF test statistic at the currency value of USD 1,0326.0, the probability of the ADF test statistic is 0.737. it is concluded that the rate of return cannot be said to be stationary, because the ADF test statistic (-1.032360) > critical value 5% (-2.903566). First difference test, the result of the ADF test statistic is -6.850636, and the probability value of the ADF Test statistic is 0.0000.